Pengaruh Citra Merek Dan Harga Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada PT. Smartfren Telecom Tbk. Cabang Kota Metro - Dina Wulan Aprianti; Selamet Fuadi; Suwarto (Jurnal Manajemen DIVERSIFIKASI, 2025)
Based on the data, increasing customers within the company is not only related to the problem of scheduling work and skills in completing marketing, but also regarding how the atmosphere or how to promote products and pay attention to prices and relationships with customers at PT. Smartfren Telecom Tbk. Metro City Branch certainly needs a good promotion and strategy to attract customers so they can compete with other providers. The number of product sales depends on how the company promotes and develops the product brand itself. This study has a goal, namely to whether there is a direct effect on brand image and price on customer loyalty and customer satisfaction. The sample of this research is the customers of PT.Smartfren Telecom Tbk. Metro City branch as many as 36 people. Data collection used a questionnaire, and data analysis used a Validity Test, Reliability Test, Normality Test, Homogeneity Test, Linearity Test and Regression Significance and Path 2 Substructural Analysis with the program (SPSS 20). The results showed that there was a direct effect of Brand Image and Work Environment on Customer Loyalty, there was a direct effect of Brand Image and Work Environment on Customer Satisfaction, and there was a direct effect of Customer Satisfaction on Customer Loyalty.